PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP HASIL BELAJAR TEMATIK KELAS V SEKOLAH DASAR - Roby Kurniawan; Tahmid Sabri; Sugiyono Sugiyono (Universitas Tanjungpura, 2020)
AbstractThe problem in this research was how the influence of contextual approach affect the thematic learning outcomes of the grade V Elementary School 36 South Pontianak. This study aims to determine the effect of contextual approaches to student learning outcomes in grade V 36 Elementary Schools in South Pontianak. The method used is experimental, while the form of research used is quasi experimental design with nonequivalent control group design. The population which is at the same time a sample in this study are all fifth grade students of the grade V Elementary School 36 South Pontianak, which consists of two classes, namely VA and VB, with a total of 51 people. Data collection tools used in the form of Multiple Choice tests totaling 50 questions. Based on statistical calculations, the average results of the experimental class post-test was 76.80 while the average post-test results of the control class were 71.00. t-test results obtained = 2,293 and α = 5% (with dk = 25 + 26 - 2 = 49) of 1,648, which means (2,293)> (1,648), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is an effect of contextual approach to the thematic learning outcomes of class V 36 Primary Schools in South Pontianak. The result of the calculation of the effect size (ES) was obtained 0.56 which was classified as medium criteria so that the contextual approach had a good influence on the learning outcomes of fifth grade students at 36 Pontianak Elementary School in South Pontianak. Keywords : Contextual Approach, Learning Outcomes, Thematic Learning